Flavonoid glycosides from Viscum album - Thu, Vu Kim; Thoa, Nguyen Kim; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Using combined chromatographic methods, four flavonoid glycosides, (2S)-homoeriodictyol-7-O-β-D-apiofuranosyl-(1→2)-O-β-D-glucopyranoside (1), (2S)-5-hydroxy-7,3′-dimethoxyflavanone-4′-O-β-D-apiofuranosyl-(1→2)-O-β-D-glucopyranoside (2), homoflavoyadorinin-B (3), and 3′-methoxyapiin (4) were isolated from the methanol extract of the leaves and twigs of Viscum album. Their structures were elucidated by 1D- and 2D-NMR spectra and in comparison with those reported in the literature. Keywords. Viscum album, flavonoid glycoside.